Statistical literacy level of mathematics education students: Challenges and recommendations for competency improvement - Azis Azis; Jarnawi Afgani Dahlan (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
An essential part of statistical literacy is a person's fundamental ability to read, understand, interpret, compile, represent, process, and critically evaluate statistical information. In addition, the ability to interpret and communicate the data that has been obtained is also part of statistical literacy. This study aims to analyze students' statistical literacy level and the challenges faced in statistical literacy and provide recommendations for improving competence. The study used a quantitative approach with an online survey involving mathematics education students. Data collection used a researcher-developed survey instrument, which was used consisting of 15 items covering essential, intermediate, and upper competencies. The population was students of the Mathematics Education study program. The sample was selected using a purposive sampling technique based on the criteria of students who have taken statistics courses. The survey was administered online. The results showed that the students' statistical literacy level was in the low category. Students have difficulty understanding the basic concepts of statistics in essential competencies, interpreting data in intermediate competencies, and communicating statistically in upper competencies. This challenge is influenced by low motivation and interest in learning. These findings suggest several strategies to improve statistical literacy competencies, including developing a more effective curriculum, increasing learning motivation, and strengthening basic math skills. Implementing these recommendations is expected to enhance the quality of statistics learning in the Mathematics Education study program and produce mathematics educators who are competent in statistical literacy.